1995
DOI: 10.1111/j.1365-3024.1995.tb01006.x
|View full text |Cite
|
Sign up to set email alerts
|

B cell mitogenic activity of Toxocara canis adult worm antigen

Abstract: The effect of Toxocara (T.) canis antigen (TcAg) on lymphocytes was studied in vitro using normal murine spleen cells and human peripheral blood lymphocytes. TcAg prepared from adult worms stimulated murine spleen cells to proliferate at concentrations of 1-125 micrograms/ml. The responder cells TcAg are B cells, because the response was depleted by the treatment of spleen cells with anti-immunoglobulin (Ig) antibody and complement and after separation on a nylon wool column. This response was not due to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In a previous study, we reported that T. canis antigen had B cell stimulating activity in vitro (6). Then, we studied the effect of T. canis antigen on the cytokine production by normal macrophages and compared this with that of LPS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we reported that T. canis antigen had B cell stimulating activity in vitro (6). Then, we studied the effect of T. canis antigen on the cytokine production by normal macrophages and compared this with that of LPS.…”
Section: Resultsmentioning
confidence: 99%
“…We have studied the immune functions of T. canis ‐infected mice and found that B cells and macrophages are nonspecifically activated, but T cell functions such as proliferation and interleukin (IL)‐2 production are depressed in vivo (5). T. canis antigens polyclonaly activate B cells to proliferate and produce Ig in vitro (6). We studied macrophage function in T. canis ‐infected mice from the standpoint of cytokine production.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that IL-4 is essentially re- (14,48). Soluble crude extracts from A. suum, the nematode Toxocara canis, and the cestode Taenia solium possess B-cell mitogenic activity (30,47,53). We found that rDiAg has the ability to proliferate splenic B cells as effectively as LPS, suggesting that rDiAg may also act as a mitogen to B cells.…”
Section: Discussionmentioning
confidence: 67%
“…It has been shown that B cells are polyclonally stimulated in hosts infected with some helminths (14,43,48). Furthermore, soluble crude extracts from several helminths can polyclonally stimulate B cells (30,47,53). These observations raise the hypothesis that nonspecific IgE production seen during helminth infections is attributed to polyclonal activation of B cells in response to worm products.…”
mentioning
confidence: 97%
“…Indeed, although D. immitis secretes large quantities of DiAg, the molecule is not detected by serum from hosts infected naturally with the worm (1,31), suggesting that the filarial molecule mimics a host molecule. Some parasitic nematodes possess B-cell mitogenlike molecules (14,20,37) and selective inducers of IL-10 (15,36). Polyclonal activation (including nonspecific IgE synthesis) and anti-inflammatory cytokine production (e.g., IL-10) may be associated with an immunosuppression in terms of the prevention of specific responses (21,29,30).…”
Section: Discussionmentioning
confidence: 99%